Carbon dots from eco-friendly precursors for optical sensing application: an up-to-date review - Ullal, Namratha; Muthamma, Kashmitha; Sunil, Dhanya (Chemical papers, 2022)
Carbon dots (CDs) are zero-dimensional quasi-spherical nanoparticles endowed with excellent advantages including good luminescence features, photostability, low cytotoxicity, remarkable aqueous solubility, favourable biocompatibility, low risk to environment and great flexibility in surface modification. Fluorescent CDs that can selectively respond to specific inorganic/organic target molecules in environmental and biological samples are of prime significance amongst the new generation intelligent sensors due to the critical involvement of different ions/molecular species in not only human health, but also in environment processes. In this context, preparation of CDs from bioprecursors has immense significance due to the involvement of green principles, inexpensive, clean, nontoxic, easily accessible, renewable and large-scale production can be realized. This article aims at exploring different types of green raw materials including plant biomass, animal products, food items and waste materials as carbon sources for the synthesis of both undoped and doped CDs. The emphasis is given on different synthetic approaches adopted for improving the quantum yield without any chemical modification, the characterization techniques, mechanistic origin of photoluminescence and fluorescence response mechanisms involved in the sensing action towards various analytes. The significant benefits and limitations of CDs obtained from eco-friendly precursors through green approaches are summarized. Various challenges and the future prospects of these carbonaceous nanomaterials as sensors are also discussed. Graphical abstract